Molecular, biochemical and genetic characteristics of BSE in Canada. - Sandor Dudas (Public Library of Science (PLoS), 2010)
The epidemiology and possibly the etiology of bovine spongiform encephalopathy (BSE) have recently been recognized to be heterogeneous. In particular, three types [classical (C) and two atypical (H, L)] have been identified, largely on the basis of characteristics of the proteinase K (PK)-resistant core of the misfolded prion protein associated with the disease (PrP(res)). The present study was conducted to characterize the 17 Canadian BSE cases which occurred prior to November 2009 based on the molecular and biochemical properties of their PrP(res), including immunoreactivity, molecular weight, glycoform profile and relative PK sensitivity. Two cases exhibited molecular weight and glycoform profiles similar to those of previously reported atypical cases, one corresponding to H-type BSE (case 6) and the other to L-type BSE (case 11). All other cases were classified as C-type. PK digestion under mild and stringent conditions revealed a reduced protease resistance in both of these cases compared to the C-type cases. With Western immunoblotting, N-terminal-specific antibodies bound to PrP(res) from case 6 but not to that from case 11 or C-type cases. C-terminal-specific antibodies revealed a shift in the glycoform profile and detected a fourth protein fragment in case 6, indicative of two PrP(res) subpopulations in H-type BSE. No mutations suggesting a genetic etiology were found in any of the 17 animals by sequencing the full PrP-coding sequence in exon 3 of the PRNP gene. Thus, each of the three known BSE types have been confirmed in Canadian cattle and show molecular characteristics highly similar to those of classical and atypical BSE cases described from Europe, Japan and the USA. The occurrence of atypical cases of BSE in countries such as Canada with low BSE prevalence and transmission risk argues for the occurrence of sporadic forms of BSE worldwide.